La extensión del glaciarismo cuaternario en el Parque Nacional de Ordesa y Monte Perdido - Martí Bono, Carlos; García Ruiz, José María (Geographicalia, 2017)
The maximal extent reached by the glaciers in the Ordesa and Monte Perdido National Park during the young Pleistocene is discussed. The great height of the Monte Perdido massif allowed the existence of deep ice tongues that had their final area around 900 m a.s.l., except for the Escuaín and Pardina-Vióglaciers, that owing to the lower altitude and extent of their respective headwaters finished higher. The absence of frontal moraines obligates us to reconstruct such extent by means of lateral moraines and other deposits (fluvioglacial terraces, screes, alluvial fans). Likewise, other glacial deposits are cited, belonging to retreat phases. A phase of altitude glaciers, other of cirque glaciers and the Little Ice Age can be distinguished.
Keywords: Quaternary glaciers; final moraines; lateral moraines; Ordesa National Park; Pyrenees.